Misinformation about fake news: A systematic critical review of empirical studies on the phenomenon and its status as a ‘threat’ - Miró-Llinares, Fernando (European journal of criminology, 2023)
After the 2016 US presidential elections, the term ?fake news? became synonymous with disinformation and a catch-all term for the problems that social networks were bringing to communication. Four years later, there are dozens of empirical studies that have attempted to describe and analyse an issue that, despite still being in the process of definition, has been identified as one of the key COVID-19 cyberthreats by Interpol, is considered a threat to democracy by many states and supranational institutions and, as a consequence, is subject to regulation or even criminalization. These legislative and criminal policy interventions form part of the first stage in the construction of a moral panic that may lead to the restriction of freedom of expression and information. By analysing empirical research that attempts to measure the extent of the issue and its impact, the present article aims to provide critical reflection on the process of constructing fake news as a threat. Via a systematic review of the literature, we observe, firstly, that the concept of fake news used in empirical research is limited and should be refocused because it has not been constructed according to scientific criteria and can fail to include relevant elements and actors, such as governments and traditional media. Secondly, the article analyses what is known scientifically about the extent, consumption and impact of fake news and argues that it is problematic to establish causal relationships between the issue and the effects it has been said to produce. This conclusion requires us to conduct further research and to reconsider the position of fake news as a threat as well as the resulting regulation and criminalization.